Identification and confirmation of quantitative trait loci for stachyose content in soybean seed. Issue 2 (9th February 2015) - Zeng, Ailan; Chen, Pengyin; Zhang, Bo; Orazaly, Moldir; Florez‐Palacios, Liliana; Brye, Kristofor R.; Singh, R.
Abstract Stachyose is an unfavorable sugar in soybean meal that causes flatulence for non‐ruminant animals. Understanding the genetic control of stachyose in soybean will facilitate the modification of stachyose content at the molecular level. The objective of this study was to identify quantitative trait loci (QTL) associated with seed stachyose content using simple sequence repeat (SSR) and single nucleotide polymorphism (SNP) markers. A normal stachyose cultivar, 'Osage', was crossed with a low stachyose line, V99‐5089, to develop a QTL mapping population. Two parents were screened with 33 SSR and 37 SNP markers randomly distributed on chromosome 10, and 20 SSR and 19 SNP markers surrounding a previously reported stachyose QTL region on chromosome 11. Of these, 5 SSR and 16 SNP markers were used to screen the F3:4 lines derived from 'Osage' x V99‐5089. Seed samples from F3:5 and F3:6 lines were analyzed for stachyose content using high‐performance liquid chromatography (HPLC). Composite interval mapping analysis indicated that two stachyose QTL were mapped to chromosome 10 and 11, explaining 11% and 79% of phenotypic variation for stachyose content, respectively. The SSR/SNP markers linked to stachyose QTL could be used in breeding soybean lines with desired stachyose contents. Chi‐square tests further indicated that these two QTL probably represent two independent genes for stachyose content. Therefore, a major QTL was confirmed on chromosome 11 and a novel QTL was found on chromosome 10 for stachyose content.